PENINGKATAN KEMAMPUAN MENULIS PUISI DENGAN MODEL CONCEPT SENTENCE BERBANTUAN PPT INTERAKTIF BERBASIS KUIS DI KELAS IV SEKOLAH DASAR - Krismia Fatmawati; Fida Rahmantika Hadi; Titik Isdarwati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to describe the improvement of poetry writing ability through the application of concept sentence model assisted by learning media in the form of interactive power point based on quiz. The research method used was classroom action research (CAR) with a research design using the Kemmis and Mc Taggart model which was carried out in 3 cycles with a duration of 2 meetings in each cycle. The subjects in this study were 28 students of class IV-B SDN 01 Taman Madiun City. The object of this study is the students' ability to write poetry. This research was conducted in the even semester of the 2023/2024 school year starting in February-April. Data collection techniques were conducted by interview, observation, written test, and documentation. The results of this study show that the scores obtained by students from poetry writing activities at the pre-cycle stage to the third cycle have increased. The percentage of completeness in the pre-cycle was 25% with an average score of 57.49; the percentage of completeness in the first cycle was 50% with an average score of 67.5; the percentage of completeness in the second cycle was 67.86% with an average score of 70.94; and the percentage of completeness in the third cycle was 85.72% with an average score of 85.27. In the third cycle, the percentage of completeness had exceeded the classical completeness indicator set (80%) and the average value obtained had reached the set completeness value (75).